Impacts of introduced sustainable land management (ISLM) practices on crop yield and net farm income of smallholder farmers, Eastern and Southern Ethiopia - Alemayehu Temesgen Gebremikael; Jemal Yousuf Hassan; Getachew Shambel Endris; Chanyalew Seyoum Aweke (Discover Sustainability)
Abstract Land degradation is a major serious threat to the world’s competence to achieve agricultural productivity and environmental sustainability. It is most severe in developing countries, mainly in Sub-Saharan Africa. To reverse the situation, targeted programs promoting introduced sustainable land management (ISLM) practices have been implemented in eastern and southern Ethiopia. However, there are limited impact assessments on the contributions of adopting ISLM practices on the welfare of farmers. This study investigates the impacts of adopting ISLM practices on crop yield and net farm income in eastern and southern Ethiopia. The data were gathered from 384 randomly selected household heads (190 adopters and 194 non-adopters) using multistage sampling procedures. Descriptive statistics and econometric models were applied to analyze the data. The key ISLM practices adopted in the study area were improved soil bunds, bench terraces, chemical fertilizers, and forage production. The results of the binary logit model revealed that age of household head, education level, livestock size, social group membership, frequency of extension contacts, access to ISLM information, access to credit, land slope, farm-house distance, farmers’ perception of land degradation, and attitude toward ISLM effectiveness significantly affected the probability of adoption of ISLM practices. The propensity score matching (PSM) model showed that ISLM practices adoption has a positive impact on crop yield and net farm income of farmers. On average, it has increased crop yield per hectare and net farm income per year of ISLM practices adopted farmers by 16.8% (418.42 kg) and 19.1% (7604.99 birr), respectively, compared to non-adopter farmers. This study concluded that farmers’ welfare was enhanced by adopted ISLM practices through SLM interventions. Therefore, it is recommended that to increase the adoption of ISLM practices and enhance farmers’ welfare, policymakers and project planners should design SLM interventions based on the identified significant covariates.